Saccaharum Cilliare Fiber Reinforced Polymer Composites - A. S. Singha; Vijay Kumar Thakur (E-Journal of Chemistry)
Renewable resources such as natural fibers in the field of fiber reinforced materials with their new range of applications represent an important basis in order to fulfill the ecological objective of creating eco-friendly materials. In views of enormous advantages a study on green composites using Saccaharum cilliare fiber as a reinforcing material and urea-formaldehyde (UF) as a novel matrix has been made. First of all urea-formaldehyde resin synthesized was reinforced withSaccaharum cilliare fiber. Reinforcement of the fiber was accomplished in three different forms particle (200 micron) reinforcement, short fiber (3 mm.) reinforcement and long fiber (6 mm) reinforcement. Present work reveals that mechanical properties such as: tensile strength, compressive strength and wear resistance of urea -formaldehyde resin (UF) increases to a significant extent when reinforced with Saccaharum cilliare fiber which is found in outsized amount in the Himalayan Region. These mechanical properties mainly depend upon the dimensions of the fiber used. Analysis of results shows that particle reinforcement is more effective as compared to short and long fiber reinforcement. Morphological and thermal studies of these composites have also been carried out.